When folic acid fails: Insights from 20 years of neural tube defect surveillance in South Carolina. (24th June 2015) - Bupp, Caleb P.; Sarasua, Sara M.; Dean, Jane H.; Stevenson, Roger E.
<x xml:space="preserve">Abstract</x> Neural tube defects (NTDs) are the most common of the severe malformations of the brain and spinal cord. Increased maternal intake of folic acid (FA) during the periconceptional period is known to reduce NTD risk. Data from 1046 NTD cases in South Carolina were gathered over 20 years of surveillance. It was possible to determine maternal periconceptional FA use in 615 NTD‐affected pregnancies. In 163 occurrent (26.9%) and two recurrent (22%) NTD cases, the mothers reported periconceptional FA use. These women were older and more likely to be white. Maternal periconceptional FA usage was reported in 40.4% of cases of spina bifida with other anomalies but in only 25.2% of isolated spina bifida cases (P = 0.02). This enrichment for associated anomalies was not noted among cases of anencephaly or of encephalocele. Among the 563 subsequent pregnancies to mothers with previous NTD‐affected pregnancies, those taking FA had a 0.4% NTD recurrence rate, but the recurrence without FA was 8.5%. NTDs with other associated findings were less likely to be prevented by FA, suggesting there is a background NTD rate that cannot be further reduced by FA. Nonetheless, the majority (73.9%) of NTDs in pregnancies in which the mothers reported periconceptional FA use were isolated NTDs of usual types. Cases in which FA failed in prevention of NTDs provide potential areas for further study into the causation of NTDs. The measures and techniques implemented in South Carolina can serve as an effective and successful model for prevention of NTD occurrence and recurrence. © 2015 Wiley Periodicals, Inc.